Existence of solutions for parabolic equations of Kirchhoff type involving variable exponent. Issue 3 (3rd March 2016) - Fu, Yongqiang; Xiang, Mingqi
Abstract : In this paper, we study a class of quasilinear parabolic equations involving -Laplacian operator and nonlocal term in a bounded domain, which arises from biomathematics or nonstationary fluids. Under appropriate assumptions, we obtain the local existence of weak solutions by applying Galerkin's approximation method.